Frequency, Characteristics, and Outcomes of Endovascular Thrombectomy in Patients With Stroke Beyond 6 Hours of Onset in US Clinical Practice. Issue 12 (December 2021) - Zachrison, Kori S.; Schwamm, Lee H.; Xu, Haolin; Matsouaka, Roland; Shah, Shreyansh; Smith, Eric E.; Xian, Ying; Fonarow, Gregg C.; Saver, Jeffrey
Abstract : Background and Purpose: In 2018, 2 randomized controlled trials showed the benefit of endovascular thrombectomy (EVT) in acute ischemic stroke patients treated 6 to 24 hours from last known well using imaging-guided selection. However, little is known about outcomes in contemporary nontrial settings. We assessed the frequency of EVT and outcomes beyond 6 hours in the US Get With The Guidelines–Stroke clinical registry. Methods: We analyzed all acute ischemic stroke patients treated with EVT between January 1, 2009 and October, 1, 2018, at Get With The Guidelines–Stroke hospitals in the United States. We assessed trends over time in frequency of EVT beyond 6 hours, compared patient characteristics and outcomes between those treated within versus beyond 6 hours, and evaluated the associations between EVT time and outcomes. Results: We identified 53 702 patients at 697 sites treated with EVT during the study period. Treatment after 6 hours from last known well occurred in 17 720 (33%) of all 53 702 EVT cases (median 4.7 hours, interquartile range, 3.3–7 hours). The proportion of EVT cases treated after 6 hours from last known well varied widely across sites (median 30%, interquartile range, 24%–38%). Compared with patients treated within 6 hours, those treated beyond six hours were younger, less likely to have atrial fibrillation, less likely to arrive by ambulance, had lower stroke severity, were less likely to be anticoagulated, and more likely to be treated at centers with higher EVT volumes. After adjusting for patient and hospital characteristics, patients receiving EVT beyond 6 hours had less favorable in-hospital mortality, ambulation at discharge, and discharge disposition compared to those treated within 6 hours. Conclusions: EVT is frequently performed for patients with ischemic stroke after 6 hours from last known well, accounting for one-third of cases nationally, and adjusted functional outcomes at discharge are worse in these patients compared to those treated with EVT within 6 hours. Further efforts are needed for optimal EVT outcomes in clinical practice settings. Abstract : Supplemental Digital Content is available in the text.